2011
DOI: 10.1253/circj.cj-10-0368
|View full text |Cite
|
Sign up to set email alerts
|

Biological Variation of Brain Natriuretic Peptide and Cardiac Events in Stable Outpatients With Nonischemic Chronic Heart Failure

Abstract: Background: To evaluate the biological variation and prognostic value of brain natriuretic peptide (BNP) for stable outpatients with nonischemic chronic heart failure (NICHF). Methods and Results:Biological variation in BNP was evaluated using an automated assay system in 140 outpatients with NICHF. The stable clinical condition during the 2-month study period was defined as unchanged NYHA and unchanged left ventricular ejection fraction; therefore, 7 patients were excluded during the 2 months. Thereafter, 133… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
1
3
0
1
Order By: Relevance
“…14 Increase in BNP is useful for predicting cardiac events in stable outpatients with non-ischemic chronic HF. 15 Logeart et al found that when HF patients have a 70% prevalence of systolic dysfunction of LVEF (<45%), high BNP at pre-discharge assessment is a strong, independent marker of death or re-admission after decompensated congestive HF, 16 which is also consonant with the present result that the prevalence of DCM with systolic dysfunction was 76.9%. In addition, Javaheri et al reported that low DBP was associated with worse survival in patients with HF and a decreased ejection fraction.…”
Section: Discussionsupporting
confidence: 87%
“…14 Increase in BNP is useful for predicting cardiac events in stable outpatients with non-ischemic chronic HF. 15 Logeart et al found that when HF patients have a 70% prevalence of systolic dysfunction of LVEF (<45%), high BNP at pre-discharge assessment is a strong, independent marker of death or re-admission after decompensated congestive HF, 16 which is also consonant with the present result that the prevalence of DCM with systolic dysfunction was 76.9%. In addition, Javaheri et al reported that low DBP was associated with worse survival in patients with HF and a decreased ejection fraction.…”
Section: Discussionsupporting
confidence: 87%
“…21 Physical activity was determined on the basis of the American College of Cardiology/American Heart Association guidelines for the diagnosis and management of CHF in the adult, 1 and all patients were in stage C. Control subjects were matched by age and gender to CHF patients without any cardiac risk factors, such as hypertension, diabetes mellitus, dyslipidemia and obesity. Plasma/serum levels of highsensitivity C-reactive protein (hs-CRP), brain natriuretic peptide (BNP) 22 and high-sensitivity cardiac troponin I (hs-cTnI), 23, 24 were also determined as markers of inflammation, HF severity and myocardial damage, respectively.…”
Section: Subjectsmentioning
confidence: 99%
“…A previous study reported that the change ratio of BNP is a predictor of cardiac events. In patients with nonischemic chronic heart failure, a ≥15% increase in BNP levels was considered a risk factor for the occurrence of cardiac events (17). In another study, involving patients with chronic heart failure, the relationship between the change ratio and mortality in the N-terminal-pro-BNP, a precursor BNP was investigated.…”
Section: Discussionmentioning
confidence: 99%